BINARY IONIC LIQUID USING QUINOLINIUM IODIDE AND 1-BUTYL-3-METHYLIMIDAZOLIUM IODIDE AS ELECTROLYTE FOR DYE-SENSITIZED SOLAR CELL - NAZLIM, MUHAMMAD ARDANY (IRC, 2017)
This project is to synthesis binary ionic liquid using 1-butyl-3-methylimidazolium iodide, [BMIM][I] and quinolinium iodide as electrolyte for DSSC to replace organic volatile solvent. Binary ionic liquid has been chosen because it posses very low vapour pressure while having the same characteristic as organic volatile solvent. Four different mixtures of binary ionic liquids were tested to find out which posses high efficiency. To do that, these mixtures were characterized to find out the viscosity, physiochemical properties, melting point using viscometer, thermogravimetric analysis (TGA) before DSSCs can be fabricated. Photovoltaic measurement will be done to get the I-V curve to determine the power conversion efficiency of the DSSC using solar simulator. Viscosity test showed at higher ratio of quinolinium iodide, the viscosity increased. TGA results showed the binary mixtures have viscosity are in between of pure ionic liquids. As for power conversion efficiency, [BMIM][I] and quinolinium iodide at ratio 1:1 gave efficiency of 1.361% and the lowest recoded was pure [BMIM][I] which is 1.003%. All electrolytes were added with the same amount of LiI and I2 which are 0.5M.